Chemicals from biomass : integrating bioprocesses into chemical production complexes for sustainable development - Sengupta, Debalina; Pike, Ralph W. , 1935- (Green chemistry and chemical engineering, 2013)
"Identifying and designing new chemical processes that use renewable feedstock as raw materials and show how these processes can be integrated into existing chemical production complexes are key to having a sustainable chemical industry. Also, identifying and designing new industrial processes that use carbon dioxide as a raw material are an important option in mitigating the effects of global warming"-- Provided by publisher